Young women's and men's opportunity spaces in dairy intensification in Kenya - Bullock, Renee; Crane, Todd A. (Wiley, 2021)
Kenya has a high youth population coupled with high rates of unemployment. Development policies, including the National Youth Policy, emphasize the potential of agriculture as a source of youth employment. Kenya's dairy subsector is relatively well developed and continuing to commercialize. We analyse young women and men's current and emerging roles in dairy intensification and develop a conceptual framework that draws on opportunity space, intersectionality and agency. We collected qualitative data in Nakuru and Kiambu counties, in rural and peri‐urban locations. Based on 20 interviews, 18 focus group discussions, and a validation workshop, we describe social relations and the intersection of social factors that influence young women and men's changing roles and opportunities. We find that youth are embedded within social relations that reflect how age, ethnicity and gender intersect and interact with location to create differential access to agricultural resources and roles and practices in dairy value chains. While our data show that norms and practices of social exclusion may be reinforced through generations, we also find examples that demonstrate young women and men's capacity as agents of change in their communities. Our research contributes to understanding young women and men's diverse experiences in dairy and potential in agriculture.